SALIVARY PERIODONTAL MARKER BACTERIA RELATED TO COMMUNITY PERIODONTAL INDEX (CPI) IN NONSMOKERS VERSUS SMOKERS ROMANIAN ADULTS - Cristina Nuca; Victoria Badea; Aureliana Caraiane (Romanian Society of Oral Rehabilitation, 2013)
Background While the relation smoking - periodontal disease is evident, the effect of smoking on oral microbiota is not fully investigated. Aim of the study To compare the presence of 10 periodontal marker bacteria in saliva of smokers vs. nonsmokers, in relation with CPI Index. Material and methods A sample of 286 adults (44.05% smokers, 55.94% nonsmokers) participated in a clinical study for collecting unstimulated saliva (2.5 ml) and recording CPI Index; the salivary samples were analysed for the presence of 10 periodontal bacteria (classified and scored by pathogenicity), by direct microscopic exam, bacterial cultures and automatic identification. Ethics approval was obtained. Statistics used SPSS 12. Results CPI and microbiological score were significant higher in smokers vs. nonsmokers, and correlated with each other (p<0.05). The presence of periodontal bacteria in the saliva samples was 67.9%, more frequent (p<0.05) in smokers (75.3%) than in nonsmokers (61.9%); E.corrodens, P.micros, T.denticola, A. actinomycetemcomitans and P.gingivalis were found more frequently in smokers saliva, the last two being related with CPI; F.nucleatum was found more frequently in nonsmokers saliva, being related with CPI; the prevalence of P.nigrescens, C.rectus and P.intermedia did not record significant differences in nonsmokers vs. smokers. Conclusions The smokers saliva varies considerably from that of non-smokers in terms of periodontal marker bacteria prevalence, this being related with the periodontal profile assessed by CPI; because the relation between the salivary periodontal markers bacteria and periodontitis in smokers vs. nonsmokers is essential for the prevention and treatment of periodontal disease, it needs further long-term studies to elucidate.